Perencanaan Persediaan Bahan Baku Palet Kayu Menggunakan Material Requirement Planning (MRP): Studi Kasus PT Bumi Mandiri Resources TBK. Abstrak - Ahmad Haris Hasanuddin Slamet; Lilis Ayu Fatinia (Ikatan Da'i Indonesia, 2025)
PT Bumi Mandiri Resources is a manufacturing company engaged in producing wooden pallets with a make-to-order production system or production after an order is received. Wooden pallets are transport aids processed from solid wood materials to facilitate logistics operations. The demand for wooden pallets in Indonesia is influenced by the level of manufacturing activity and export-import conditions that cause fluctuations in demand for pallets that are not fixed. PT BMR faces challenges in raw material inventory because it still uses conventional and unsystematic methods. This study aims to design a more efficient raw material inventory planning for one year using the Single Exponential Smoothing (SES) forecasting method and the Material Requirement Planning (MRP) planning method. The MRP method calculation will be carried out using the Economic Order Quantity (EOQ) and Lot for Lot (LFL) techniques to compare the results of the best raw material planning design. The calculation results show that the SES method with the parameter α (0.09) provides the lowest error rate. This indicates that the MRP method calculation using the EOQ technique provides higher efficiency with cost savings in one year period of 49.54% compared to the LFL technique.